COMMENTARY: I'M ONLY TRYING TO HELP: A ROLE FOR INTERVENTIONS IN TEACHING LISTENING - Michael Rost (Language Learning and Technology, 2007)
In my work as an author and teacher trainer, I have the opportunity to travel around the world and talk to teachers in a variety of settings. Though I meet teachers with a range of backgrounds and a wide disparity of resources, I find that a few common themes come up whenever I talk with teachers about language teaching and technology. One of the familiar refrains is that most of us claim to lack the technological resources we feel we need to teach effectively. There’s always something new on the horizon that we feel we just have to have. Another recurring theme is the lament that most of our students just don’t seem to take advantage of the extra learning opportunities we present them anyway! Teachers want to help, but often feel under appreciated for their efforts. Personally, I have relished the ongoing advances in technology over the course of my teaching career. I started out as a secondary school teacher in Togo, West Africa with chalk – sometimes yellow or pink! – and a blackboard as my only teaching technology. When teachers express a sense of being overwhelmed by new technology, I sometimes talk about my own beginnings and also remind them of a few of Donald Norman’s principles of human-centered design. According to Norman (2004), for any new technology to be effective, it must be intuitively helpful and elegantly efficient. In the case of language teaching, this means the technology must – immediately and transparently – help us teach better than we do already. If it doesn’t, we simply shouldn’t use it. In addition, Norman says, for any new technology to be widely adopted, it must appeal to the emotions as well as to reason. If people don’t enjoy using a particular technology, no matter how logically useful it may be, they will tend to shun it. Perhaps because as language teachers we tend to favor eclecticism, we will often throw any emerging technology into the mix as a "helpful resource." As Doughty and Long (2003) point out, teachers often do not distinguish between new technological tools that are innovative but not actually helpful and those which are innovative and genuinely helpful. In my own instructional design, I have identified three "intervention phases" in the listening process: decoding, comprehension, and interpretation. Before we assume any new technology or intervention is actually going to be supportive, I believe we need to understand the learners' goals during these listening processes. What actually motivates the learners towards achieving these goals is what ultimately will be useful.